Epidemiology of Acute Extensor Mechanism Injuries in Collegiate-Level Athletes in the United States. (March 2022) - Chen, Kevin K.; Chan, Jimmy J.; Ranson, William; Debellis, Nicholas; Huang, Hsin-Hui; Vulcano, Ettore; Colvin, Alexis
Background: Extensor mechanism injuries involving the quadriceps tendon, patella, or patellar tendon can be a devastating setback for athletes. Despite the potential severity and relative frequency with which these injuries occur, large-scale epidemiological data on collegiate-level athletes are lacking. Study Design: Descriptive epidemiology study. Level of Evidence: Level 4. Methods: Knee extensor mechanism injuries across 16 sports among National Collegiate Athletic Association (NCAA) men and women during the 2004-2005 to 2013-2014 academic years were analyzed using the NCAA Injury Surveillance Program (NCAA-ISP). Extensor mechanism injuries per 100, 000 athlete-exposures (AEs), operative rate, annual injury and reinjury rates, in-season status (pre-/regular/postseason), and time lost were compiled and calculated. Results: A total of 11, 778, 265 AEs were identified and included in the study. Overall, 1, 748 extensor mechanism injuries were identified, with an injury rate (IR) of 14.84 (per 100, 000 AEs). N = 114 (6.5%) injuries were classified as severe injuries with a relatively higher median time loss (44 days) and operative risk (18.42%). Male athletes had higher risk of season-ending injuries in both all (3.20% vs 0.89%, P < 0.01) and severe (41.54% vs 16.33%, P < 0.01) extensor mechanism injuries. Similarly, contact injuries were more frequently season-ending injuries (4.44% vs 1.69%, P = 0.01). Women's soccer (IR = 2.59), women's field hockey (IR = 2.15), and women's cross country (IR = 2.14) were the sports with the highest rate of severe extensor mechanism injuries. Conclusion: Extensor mechanism injuries in collegiate athletes represent a significant set of injuries both in terms of volume and potentially to their athletic careers. Male athletes and contact injuries appear to have a greater risk of severe injuries. Injuries defined as severe had a higher risk of operative intervention and greater amount of missed playing time. Clinical Relevance: Knowledge of the epidemiology of extensor mechanism injuries may help clinicians guide their athlete patients in sports-related injury prevention and management.